Current Knowledge on River Buffalo Meat: A Critical Analysis - Liliana Di Stasio; Alberto Brugiapaglia (Animals, 2021)
The estimated world population of water buffalo counts around 204 million head, mostly reared for milk production. However, buffaloes also largely contribute to the meat sector, with around 4.3 million tonnes produced in 2019, mainly derived from old animals at the end of their productive or working life and only to a small extent from young animals. Therefore, buffalo meat production has been generally considered unsatisfactory for both quantity and quality. In fact, the dressing percentage is generally lower than 50% and the meat is considered of poor quality mainly due to its dark colour and reduced tenderness. However, in recent years, the healthy properties highlighted by some studies have led to a renewed interest in buffalo meat, with a parallel increase in research. Therefore, this review aims at providing an updated picture on carcass and meat quality traits in river buffalo, with special attention to the intrinsic and extrinsic factors contributing to their variability. The research done so far has demonstrated that river buffaloes can efficiently contribute to the quanti-qualitative production of meat, provided that the meat supply chain is specifically organised for this purpose. The analysis of the available data also showed that further research is needed on the factors affecting meat production in order to gain greater knowledge essential for planning more targeted interventions.